MULTIPLE ACTS OF SEXUAL PENETRATION WITHIN A SHORT PERIOD OF TIME – SINGLE OR MULTIPLE ACTS OF RAPE? S v Willemse 2011 (2) SACR 531 (ECG) - GP Stevens (Obiter, 2021)
The case under discussion exposes a particular twilight zone in respect of the sexual offence of rape, and more specifically, the question as to when multiple acts of sexual penetration perpetrated by the same perpetrator within a relatively short time span, will constitute multiple acts of rape. The latter, in addition, specifically becomes problematic during sentencing. Once it has been established that a victim was raped more than once by an accused, a court is obliged in terms of section 51(1) of the Criminal Law Amendment Act 105 of 1997 (hereinafter “the Act”) to impose a sentence of life imprisonment, unless substantial and compelling circumstances exist to depart from the prescribed minimum sentence. The decision under discussion is of particular interest as the court was once again required to assess whether multiple acts of sexual penetration constituted a single act of rape, or multiple acts of rape and as such falling within the ambit of the provisions of the Act with regards to sentencing. A related issue addressed by the judgment, relates to the anomaly in respect of the appropriate approach to follow in cases of this nature relating to multiple acts of sexual penetration in order to assess whether these acts should be construed as multiple acts of rape, or as one single and prolonged act of rape.